Rationality of Use and Effectiveness of Stress Ulcer Prophylaxis in Critically Ill Patients: An Experience from A Tertiary Intensive Care Unit - Heru Prabowo; Cecilia Oktaria Permatadewi; Hesti Triwahyu Hutami; Didik Indiarso; Agung Prasetyo; Hirlan Hirlan; Hery Djagat Purnomo (Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Stress-related mucosal disease (SRMD) frequently develops in critically ill patients, increasing mortality and length of intensive care unit (ICU) stay. There is limited data on stress ulcer prophylaxis (SUP) on critically ill patients in Indonesia.Objective:Methods: This is a retrospective cohort study of patients admitted to the ICU from January 1, 2015, to December 31, 2017. The subjects were all ICU patients who used proton pump inhibitor (PPI) and histamine-2 receptor antagonist (H2RA) as SUP therapy.Results: A total of 315 patients were included, and mean age was 48 years. Approximately 55.2% were women, and 62.8% of patients were admitted to ICU following high-risk surgery. PPI was given to 187 patients (59.4%) and H2RA to 128 patients (40.6%), with an average usage for 5 days. The incidence of SRMD was 15.9% (n = 50), and mean length of stay in the ICU was 6 days. Gender, age, duration of SUP, and ICU length of stay of the PPI and H2RA groups were not statistically different (p > 0.05) and did not affect the GI event (p > 0.05). The use of rational SUP was 98.4%. Major American Society of Health-System Pharmacists (ASHP) risk factor criterion was ventilator use (86.8%), while the minor ASHP criterion was anticoagulant therapy (22.2%). The incidence of GI event was significantly lower in PPI groups than H2RA groups (p < 0.05).Conclusions: The use of SUP is rational with an average use of 5 days. PPI are superior to H2RA for SRMD prophylaxis.